Hawai'i eight hundred years of political and economic change - La Croix, Sumner J., 1954- (Markets and governments in economic history., 2019)
Relative to the other habited places on our planet, Hawai'i has a very short history. The Hawaiian archipelago was the last major land area on the planet to be settled, with Polynesians making the long voyage just under a millennium ago. Our understanding of the social, political, and economic changes that have unfolded since has been limited until recently by how little we knew about the first five centuries of settlement. Building on new archaeological and historical research, Sumner La Croix assembles here the economic history of Hawai'i from the first Polynesian settlements in 1200 through US colonization, the formation of statehood, and to the present day.